PENGARUH SMALL GROUP DISCUSSION TERHADAP TINGKAT PENGETAHUAN TENTANG TIGA MASALAH KESEHATAN REPRODUKSI REMAJA: The Effect of Small Group Discussion on The Level of Knowledge About Three Adolescent Reproductive Health Problems - Yohana Rambu Anarara Retang; Oktalia Damar Prasetyaningrum; Chatarina Hatri Istiarini; Priyani Haryanti (Forind Press, 2024)
The development of adolescent is highly susceptible to issues. One of them is reproductive health problems. Based on the results of a preliminary study on 23 adolescents at the research location, the data showed 26.1% of them were smokers; 52.2% were alcoholic, 69.6% watched pornographic videos; 88.2% had held hands with their opposite sex; 82.4% had hugged; 58.8% had kissed; 23.5% of them have ever touched reproductive organs and breasts; and 2 cases of unwed pregnancy in 2021. This research aim to determine the effect of small group discussion toward with the knowledge level related to the three reproductive health problems of adolescents in Wates Kulon Progo. This research methods uses quasi experimental research design with one group pretest and posttest approach. The population is 126 adolescents of 11-21 aged. The sampling technique was purposive sampling. The number of samples is 47 people using G Power. Measuring instrument using questionnaires. Statistical test using Wilcoxon test. The result showed most of the respondents 14-17 aged were female with a high school education level. Obtained p value of 0.000 <0.05 then Ho is rejected, thus the Small Group Discussion method has an effect for the knowledge level toward with the knowledge level related to the three reproductive health problems of adolescents in Wates Kulon Progo.